2009
DOI: 10.12702/1984-7033.v09n02a04
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and combining ability in some powdery mildew resistant wheat lines

Abstract: -Three commercial varieties susceptible to powdery mildew and five high-yielding genotypes with resistance to powdery mildew from the CIMMYT were used in this study to estimate the general combining ability of parents, to detect gene actions of resistance against powdery mildew and identify the most suitable genotype for transferring resistance genes to the commercial varieties. In conclusion, monogenic inheritance was detected in the F 2 generation in crosses of parent 48 with two commercial varieties, Atilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Among the wheat traits, grain yield is one of the most important and complex polygenic trait, influenced by many components. Since that favorable combination of yield components may improved grain yield, analyzing various traits related to grain yield, as well as the selection of genetically suitable parents in crosses are the initial breeding steps which could ensure success in breeding programs (Ilker et al, 2009). Keeping this in view, wheat breeders have been concentrated on development of high yielding wheat cultivars by crossing good general combining parental lines and selecting desirable transgressive segregants from resulting hybrids for grain yield traits (Istipliler et al, 2015;Kumar et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Among the wheat traits, grain yield is one of the most important and complex polygenic trait, influenced by many components. Since that favorable combination of yield components may improved grain yield, analyzing various traits related to grain yield, as well as the selection of genetically suitable parents in crosses are the initial breeding steps which could ensure success in breeding programs (Ilker et al, 2009). Keeping this in view, wheat breeders have been concentrated on development of high yielding wheat cultivars by crossing good general combining parental lines and selecting desirable transgressive segregants from resulting hybrids for grain yield traits (Istipliler et al, 2015;Kumar et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies confirmed that cultivar 'Amigo', has Pm17 and leaf rust resistance gene Lr24 on a translocated chromosome involving 1 A and 1B, respectively (Hsam and Zeller, 2006), the Pm8/ Pm1 alleles at the locus (Mohler et al, 2008) and Amigo is a source of Sr24/Lr24 (The et al,1991). There are many explanations for the number of genes that conditioned resistance to powdery mildew in wheat (Peusha et al, 2002, Srnic, 2003Ilker et al, 2009). Adult plant resistance (APR) to cereal fungal diseases provide protection in a crop's post-seedling stages typically between tillering and booting according to Adult Plant Resistance Fact Sheets GRDC, Nov. (2012).…”
Section: Introductionmentioning
confidence: 96%
“…However, the grain yield of wheat, along with spike architecture, is a very complex and polygenic trait influenced by many yield components (Reynolds et al ., 2009;Kumar et al ., 2022) . A favourable combination of yield components may improve grain yield, but the increment in one component might have a positive or negative effect on the other components (Ilker et al ., 2009;Ljubičić et al ., 2017) . Cereals possess a degree of developmental plasticity that allows for increases in kernels spike -1 or kernel weight to compensate for losses in tiller number .…”
Section: Introductionmentioning
confidence: 99%